Effects of Classroom Assessment Practices in a Foreign Language Reading Course (GIST – Education and Learning Research Journal, 2015)
This article analyzes the various types of information that alternative assessment and traditional assessment practices provided ina an English foreign language (FL) reading course for graduate students at a public univeristy in Medellín, Colombia. This study followed the principles of qualitative research, and a case study was used as a research method. There were five instruments to collect data: questionnaires, observations, tests, focus groups, and the diary of the teachers. Findings suggest that the assessment practices applied in this course helped students and teachers recognize that learning occurred. The assessment practices also helped language practitioners learn more about the teaching and learning processes in FL reading. Conclusions suggest that language practitioners should include both alternative and traditional assessment in order to have a wider picture of the process of teaching and learning.
Keywords: Alternative/traditional asssessment; foreign language reading